Marvel's The Avengers [videorecording (DVD)] - Whedon, Joss, 1964-; Downey, Robert, Jr., 1965-; Johansson, Scarlett, 1984-; Renner, Jeremy; Ruffalo, Mark; Hemsworth, Chris; Hiddleston, Tom; Paltrow, Gwyneth, 1972-; Jackson, Samuel L.; Skarsgård, Stellan; Bettany, Paul, 1971- (Distributed by Buena Vista Home Entertainment, 2012)
Nick Fury of S.H.I.E.L.D. brings together a team of superhumans to form The Avengers to help save the Earth from Loki and his army.